Efforts to Improve the Achievement of Science Learning Outcomes in Grade IV Elementary School are Assisted Through Guessing Games - Arni, Yusni; Amalia, Luthfia; Putri, Zahra Salsabila; Devi, Sri (Pusdikra-Publishing.com, 2024)
Despite the usage of learning media, science learning outcomes remain low. The kids' learning outcomes, which are still below the KKM, demonstrate this fact. Therefore, the goal of this study is to enhance class IV students' scientific learning outcomes by using picture guessing games. In order to improve science learning outcomes relating the properties of light in class IV at SD 1 Sungai Pedada Kec. Tulung Selapan Kab. OKI Semester I for the 2023-2024 academic year, the researcher intends to conduct research in class IV at SD 1 Sungai Pedada by adopting an image guessing game. This study, which encompasses two cycles of classroom action research, use observation techniques to measure increases in teacher and student engagement, exams to measure increases in student learning outcomes, and the gathering of research-related data. Thirteen male and twelve female fourth-graders made up the research subjects. Complete learning outcomes of 71,20 in cycle I and 86,48 in cycle II could be obtained based on the data analysis results; there was a 15.28% difference in the average interval score percent. There was a 5,08% rise based on the pre-cycle comparison of cycles I and II. It has been determined that using the picture guessing game in science classes in class IV SD 1 Sungai Pedada can enhance student learning outcomes.